CHARACTERISTICS OF THE DECISION TO CANCEL THE DETERMINATION OF A CORRUPTION ERADICATION SUSPECT THROUGH PRE-TRIAL (A Study of the Political-Legal Relationship between the Corruption Eradication Commission and the Institution) - Ronny Yoesfianda; Henry Aspan; T. Riza Zarzani (International Journal of Synergy in Law, Criminal, and Justice, 2025)
Several suspect determinations by the Corruption Eradication Commission (KPK) were annulled by pretrial motions due to non-compliance with applicable legal provisions, such as insufficient preliminary evidence and procedures for determining suspects that were inconsistent with criminal procedural law. These decisions emphasize the importance of protecting human rights, the principle of collective collegiality in decision-making, and judicial oversight of law enforcement actions. The research uses normative legal methods, examining the provisions of Law Number 30 of 2002 concerning the Corruption Eradication Commission (KPK), Law Number 10 of 2015, Law Number 19 of 2019, and the Criminal Procedure Code (KUHAP). Pretrial motions are also examined to understand the application of the law in concrete cases involving the annulment of suspect determinations by the KPK. Regulatory changes through Law No. 30 of 2002, Law No. 10 of 2015, and Law No. 19 of 2019 demonstrate efforts to balance the independence of the Corruption Eradication Commission (KPK) with the need for oversight and accountability. While aimed at increasing the KPK's effectiveness and accountability, these changes present challenges such as the potential for politicization and intervention. Constitutional Court Decision No. 21/PUU-XII/2014 emphasized the importance of sufficient preliminary evidence in determining suspects, which has become the basis for many pretrial decisions that have overturned the KPK's suspect determinations. Furthermore, research evaluates how the principle of collective collegiality and a proper understanding of the object of investigation are crucial to ensuring the legitimacy of the KPK's legal actions.